2019
DOI: 10.3233/ch-190580
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach of platelet function test for prediction of attenuated response to clopidogrel

Abstract: BACKGROUND: Elevated mean platelet volume (MPV) and immature platelet fraction (IPF) are predictive for vascular risk. Both can be associated with residual platelet reactivity. We aimed to explore associations among platelet characteristics and responder status in stroke patients on clopidogrel. METHODS: Blood samples from 46 patients and 15 healthy subjects were analyzed for platelet count, MPV, IPF, large cell ratio (LCR) and high-fluorsecent immature platelet fraction (H-IPF). As a novelty, not only whole b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…The study protocoll was approved by the University of Pecs Clinical Centre Regional and Institutional Research Ethics Comittee (8). Written informed consent was obtained from each patient.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study protocoll was approved by the University of Pecs Clinical Centre Regional and Institutional Research Ethics Comittee (8). Written informed consent was obtained from each patient.…”
Section: Subjectsmentioning
confidence: 99%
“…However, the prevalence of HTPR was shown to vary depending on the definition and assay used (7). A modified platelet function test (mPFT) was recently found to be superior compared to conventional Multiplate Electrode Aggregometry for selection of post-stroke patients with HTPR (8).…”
Section: Introductionmentioning
confidence: 99%
“…Platelet function guided antiplatelet therapy is getting more important because of increased resistance from antiplatelet drugs like aspirin and clopidogrel which is included in most AIS patients, and they experience different adverse vascular events due to the treatment failure. It also helps in the tailored or personalized antiplatelet therapy in the patients who have high on-treatment platelet reactivity and in the early detection of adverse vascular events ( 7 , 8 ). So, it is important to measure the inhibition of the platelet function in patients with AIS who have HTPR ( 72 ).…”
Section: Antiplatelet Resistancementioning
confidence: 99%
“…So, it is important to measure the inhibition of the platelet function in patients with AIS who have HTPR ( 72 ). The different platelet function testing methods are bleeding time, light transmission platelet aggregation (LTA), impedance platelet aggregation, lumi-aggregometry, and tests based on platelet function methods combined with viscoelastic tests, such as Thromboelastographs (TEGs)/platelet mapping systems, Rotational Thromboelastometry (ROTEM) platelets, and others, where Flow Cytometry is used to test the platelet activation, and Radio- or Enzyme-Linked Immuno Assay measure the thromboxane A2 metabolites ( 8 , 57 , 73 75 ).…”
Section: Antiplatelet Resistancementioning
confidence: 99%
“…In our own cohort, we combined the examination of endothelial and platelet-derived microvesicles and ex vivo platelet function in post-stroke patients taking clopidogrel. Both measurements were performed in whole blood and from the lower and upper blood fractions separated after 1-hour gravity sedimentation by the analogy with erythrocyte sedimentation rate (ESR) (29). We observed that the total MV number measured in the lower fraction after sedimentation showed a negative correlation with the area under the curve (AUC, reflecting the aggregation) value measured by Multiplate (Roche, Switzerland).…”
Section: Screening For High-on-treatment Platelet Reactivitymentioning
confidence: 99%